DETERMINANTS OF NON-PERFORMING FINANCING ON SHARIA BANKING IN INDONESIA - lusiana, dewi (I-Economics, 2024)
As an alternative economy, the development of Sharia banking assessed the more fast however of course no regardless of various problems risk financing. Non-performing financing is a used reference in measuring financing problems indicated by experiencing fluctuations in each period. This matter is caused by several factors, including CAR, FDR, BOPO, inflation, and BI rate. The research purpose this to know the influencing factors​ of Non-Performing Financing in banking Sharia in Indonesia. The research method used​ is multiple linear regression using time series data from 2008-2023. Research data was obtained from statistics banking Sharia, Bank Indonesia, and the Central Statistics Agency. Research results explain that in a way the CAR variable has an effect negative significance on NPF, while the BI rate has an effect positive significance against NPF. Meanwhile, FDR, BOPO, and inflation had no influential significance against NPF. As for simultaneously, all over variable study influential significance on banking NPF Sharia.